Right Hemisphere and Speech Recovery in Post-Stroke Aphasia - Shipkova, K.M.; Bulygina, V.G. (Klinicheskai͡a︡ i spet͡s︡ialʹnai͡a︡ psikhologii͡a, 2023)
The analytical review presents the clinical, neurobiological, and neuropsychological aspects of post-stroke aphasia as well as the role of the right hemisphere in speech recovery. The paper shows the influence of size, topography, lesion depth, cerebral hemodynamic plasticity, initial morphometric characteristics of the brain, and handedness on the functional recovery of aphasia. The review considers the typology and mechanisms of the appearance of "stealing symptoms" of homologous and non-homologous regions of the intact hemisphere. The "low-level" and "high-level" models of language competence of the right hemisphere are analyzed. The study describes the topography of the brain activation regions in the intact hemisphere during various speech task-solving. The paper shows the heterochrony between impressive and expressive speech recovery in aphasics and its bilateral inter-lateral distribution. The authors conclude that to clarify the mechanisms of aphasia recovery, it is necessary for a comprehensive account of clinical, neurobiological and neuropsychological patterns of speech disorder reparation in different post-stoke epochs. The paper notices that a deeper understanding of the impact of structural and functional repairment of speech processes on the aphasia outcome, it needs to assess the relationship between the degree of speech disorders reduction and the lateral vector of speech architectonics in the post-stroke period. Представлен аналитический обзор клинического, нейробиологического и нейропсихологического аспектов сосудистой афазии относительно роли правого полушария в восстановлении речи. Описана роль факторов давности афазии, локализации, объема и глубины очагового поражения, мозговой гемодинамической пластичности, инициальных морфометрических характеристик мозга и рукости в функциональном восстановлении речи. Рассматриваются типология и механизмы формирования «симптомов обкрадывания» гомологичных и не гомологичных отделов интактного полушария. Анализируются «низкоуровневая» и «высокоуровневая» модели языковой компетенции правого полушария, а также топография зон активации здорового полушария при решении различных речевых задач. Показана гетерохронность восстановления импрессивной и экспрессивной сторон речи при афазии. Отмечается, что восстановление речи носит двусторонний, латерально-распределенный характер. Авторы приходят к выводу, что для уточнения механизмов восстановления речи при афазии необходим всесторонний учет клинических, нейробиологических и нейропсихологических закономерностей репарации речевых нарушений на разных стадиях сосудистой афазии. Сделано заключение, что для более глубокого понимания влияния структурно-функциональной переорганизации речевых процессов на исход афазии необходимы исследования, направленные на оценку связи между степенью редукции нарушений речи и латеральным вектором речевой архитектоники в постинсультном периоде.